DRYING CHARACTERISTICS INVESTIGATION OF BLACK MULBERRY DRIED VIA INFRARED METHOD - Doymaz, I; Kipcak, A. S. (YILDIZ TECHNICAL UNIV, 2019)
In this study, the drying characteristics of black mulberry were studied by using the drying method of infrared. Infrared power levels were selected between 50 and 104 W. The obtained drying data were applied to several drying models (Aghbashlo et al., Page, Parabolic, Wang and Singh and Weibull), which gave the high the coefficient of determination (R-2) values. The best modelling method were selected based on the highest R-2, and the lowest reduced chi-square (chi(2)), and root mean square errors. Also, the effective moisture diffusivity was calculated using the Fick's second law's spherical coordinate approximation The activation energies were calculated from the values of the effective moisture diffusivity with respect to mass over power levels. From the results it was seen that the Parabolic type of drying model best fits the data obtained with the R-2 values between 0.997849 (104 W) - 0.999664 (62 W). The effective moisture values were obtained between 1.14 x10(-9) - 3.08x10(-9) m(2)/S and increased as the infrared power level increased. The activation energy was calculated as 2.015 kW/kg.
Keywords: Drying; Black Mulberry; Infrared; Modelling; Effective Moisture Diffusivity; Activation Energy; MOISTURE DIFFUSIVITY; KINETICS; ENERGY; Thermodynamics